Avoiding Pitfalls in Insulinomas by Preoperative Localization with a Dual Imaging Approach. Issue 7 (July 2019) - Ramonell, Kimberly M.; Saunders, Neil D.; Sarmiento, Juan; Bercu, Zachary; Martin, Louis; Weber, Collin J.; Sharma, Jyotirmay; Patel, Snehal G.
Insulinomas are rare endocrine malignancies of the pancreas that require surgical resection but can be difficult to localize preoperatively. We sought to review and improve the accuracy of preoperative localization techniques at our institution. We retrospectively reviewed all insulinomas that underwent resection at our institution between 1998 and 2016. Localization techniques include selective arterial calcium stimulation (CaStim), CT, MRI, angiography, and somatostatin receptor scintigraphy. Thirty-eight patients had pathologically proven insulinomas on surgical resection. Localization accuracies of CaStim, CT, and MRI were 89 per cent (31/35), 67 per cent (22/33), and 46 per cent (11/24), respectively. When compared with CTalone and CaStim alone, the combination of these two modalities resulted in 100 per cent preoperative localization (30/30), whereas the use of CaStim alone resulted in 80 per cent (4/5) localization and the use of CT alone resulted in 66 per cent (2/3) localization. Four of our patients had both negative CT and MRI. Among these patients, CaStim was 100 per cent localizing and the only positive modality for these patients. These data confirm that CaStim is accurate in preoperatively identifying single and multiple insulinomas; and when combined with CT, this accuracy is increased to 100 per cent. Based on these data, we propose that a dual imaging approach is a superior means of preoperative localization.